Recalcitrant organics removal using adsorption and biofilm process - Chia, Sheau Khong; Rahman, Rakmi Abd.; Mohamad, Abu Bakar; Takriff, Mohd Sobri (Penerbit Universiti Sains Malaysia, 2004)
Recalcitrant organics compounds is one of the harden problem faced by the wastewater treatment engineer because of these compounds are hard to treat and can passed through the conventional WWTP. Some of the recalcitrant organics, such as pentachlorophenol had found toxicgenic and carcinogenic to human and animals. The carbon adsorption was one of the common conventional methods for removing of these compounds. However, the treatment does not destroy these recalcitrant organics but just merely transferring it to another medium.